Treatment of the cytokine storm in COVID-19: review of clinical pharmacology - Aisyah Nur Sapriati; Fita Rahmawati; Titik Nuryastuti (Fakultas Farmasi Universitas Andalas, 2023)
The cause of the COVID-19 pandemic can be attributed to the Acute Respiratory Syndrome Virus-2 (SARS-CoV-2). COVID-19 manifests with severe symptoms in the upper respiratory tract and can progress to a critical condition due to an acute hyperinflammatory response that triggers a cytokine storm. The cytokine storm refers to an excessive or impaired production of proinflammatory cytokines, resulting in immune dysregulation and uncontrolled inflammatory activity. To effectively address the hyperinflammatory state induced by SARS-CoV-2 infection, it is imperative to explore promising strategies aimed at overcoming the cytokine storm, such as the prompt initiation of anti-inflammatory therapy. Several classes of drugs can potentially prevent the deterioration of COVID-19 patients by mitigating immune system dysregulation and suppressing uncontrolled inflammatory responses. These drug classes encompass corticosteroids, chloroquine and hydroxychloroquine, inhibitors of interleukin-1 (IL-1), inhibitors of interleukin-6 (IL-6), inhibitors of tumor necrosis factor (TNF), and anti-inflammatory drugs. Additionally, tumor necrosis factor alpha (TNF-α) inhibitors, as well as inhibitors targeting the Janus kinase signaling pathway and activator of transcription (JAK/STAT), have exhibited efficacy in treating COVID-19. This efficacy is evident when considering the drug's mechanism of action and pharmacokinetics, while also taking into account the tolerable side effects associated with their usage